2018
DOI: 10.1016/j.aeue.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of directional antennas on outband D2D mmWave communications in heterogeneous networks

Abstract: Device-to-Device (D2D) communications are considered as a keystone of the fifth generation wireless technology (5G). This new approach is very promising in terms of energy and spectrum efficiency. However, the integration of such communications in a typical cellular network increases inevitably the amount of interference. Several researches propose to lower the interference thanks to either sharing the cellular spectrum intelligently, or using non-cellular bands for D2D links. In this paper, we focus on the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Previous studies are modified to suit the proposed system model. The distribution of the received signal is following the Poisson process on R+ for the first and second hops, respectively, as below Θ1=1Y1={}PX1SX11false|X1false|,2.05482ptX1Φ1, Θ2=1Y2={}PX2SX22false|X2false|,2.05482ptX2Φ2. …”
Section: Heterogeneous Cellular Network Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies are modified to suit the proposed system model. The distribution of the received signal is following the Poisson process on R+ for the first and second hops, respectively, as below Θ1=1Y1={}PX1SX11false|X1false|,2.05482ptX1Φ1, Θ2=1Y2={}PX2SX22false|X2false|,2.05482ptX2Φ2. …”
Section: Heterogeneous Cellular Network Modelmentioning
confidence: 99%
“…To reduce the dependence on simulations, SINR closed form using stochastic geometry were derived. 4,11 It is concluded that the grid and Wyner models are not practicable for characterizing the SINR, thus stochastic geometry has emerged as a powerful tool to model and approximate the actual networks in terms of coverage probability and interference in cellular networks. 8 To provide insight-fullness into the operation of the network in the form of scaling laws, PPP model is applied.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations